Etiologies of neonatal cholestasis at a tertiary hospital in Bangladesh - Md. Benzamin; Mukesh Khadga; Fahmida Begum; Md. Rukunuzzaman; Md. Wahiduzzaman Mazumder; Khan Nahid Lamia; Md. Saidul Islam; AZM Raihanur Rahman; ASM Bazlul Karim (Paediatrica Indonesiana, 2020)
Background Neonatal cholestasis is an important etiology of chronic liver disease in young children. It has a varied etiology. There is considerable delay in presentation and diagnosis of neonatal cholestasis in Bangladesh. Lack of awareness and knowledge among the pediatricians regarding etiological diagnosis and outcome of neonatal cholestasis is the reasons for poor outcome in major portion of cases in Bangladesh. Objective To evaluate the etiological spectrum of neonatal cholestasis. Methods This retrospective study was conducted at the Department of Pediatric Gastroenterology and Nutrition, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh. We reviewed medical records of children who were diagnosed with neonatal cholestasis. Complete diagnostic profiles of every cases with age of presentation, male-female ratio and final diagnosis were analyzed. Results A total of 114 children with neonatal cholestasis were evaluated. Subjects' male-female ratio was 1.92: 1.0, and mean age at hospitalization was 92.7 (SD 39.5) days. Biliary atresia was the most common etiology (47.4%), followed by idiopathic neonatal hepatitis/INH (21.9%). Other identified etiologies were, toxoplasmosis, others (syphilis, varicella-zoster, parvovirus b19), rubella, cytomegalovirus (CMV), and herpes/TORCH infection (8.61%), progressive familial intrahepatic cholestasis/PFIC (4.4%), galactosemia (4.4%), choledochal cyst (3.5%), sepsis (1.8%), urinary tract infection/UTI (1.8%), hypothyroidism (1.8%), lipid storage disease/Niemann-Pick disease (0.9%), non-syndromic paucity of interlobular bile ducts (2.67%), and Caroli's disease (0.9%). Conclusion In Bangladesh, neonatal cholestasis cases are most often due to obstructive causes, particularly biliary atresia. Idiopathic (INH), infectious (primarily TORCH), metabolic, and endocrine causes followed in terms of frequency.